Attitudes and perceptions of library users toward fines for overdue materials in the College of Mass Communication Library University of the Philippines Diliman - Israel, Rommel L.; Santos, Herminia H. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1999)
This thesis, Attitudes and Perceptions of Library Users Toward Fines for Overdue Materials in the College of Mass Communication Library University of the Philippines Diliman, relates the library policy on the imposition of fines on overdue borrowings with the attitudes and perceptions of library users.
Through the descriptive survey method, the results shows that the present system of imposing fines is generally accepted by the majority of library users at the College of Mass Communication Library. Levying of fines on overdue books is believed to result in increased library use as the rate of immediate return of books increases and more books are made available for circulation. However, the student-respondents attitude and perception for returning books on time does not indicate their desire and awareness to contribute their share in the wider circulation of books among their co-library users. Their main reason for avoiding overdue borrowings, is the inconvenience of payment of fines or suspension of library privileges which they might experience - a matter-of-fact attitude or practical cause that may be devoid of responsibility towards others. The library's information system which facilitates among its inputs the policy on the imposition of fines appears to be weak on the dissemination of awareness in developing positive attitude towards it. An area of concern is the apparent lack of affective values to share the library's resources with fellow-users.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Libraries and education -- Philippines -- Quezon City; Library fines -- Philippines -- Quezon City